Room-temperature dissolution of PbI2 by a PEGylated deep eutectic solvent with high efficiency. (22nd June 2022) - Chen, Yu; Li, Guihua; Qiu, Yuhui; Shi, Ruifen; Li, Yuting; Bi, Zixin; Guo, Yuting; Zhang, Yixuan; Mu, Tiancheng
Abstract : PEGylated deep eutectic solvents could dissolve toxic PbI2 efficiently at room temperature. Abstract : The dissolution of lead iodide (PbI2 ) is very important for the purpose of avoiding environmental pollution. Here, an environmentally benign polyethylene glycol-based deep eutectic solvent (PEGylated DES) has been found to dissolve PbI2 with a 54.35% mass fraction at room temperature (25 °C), which is 716.1 times that in water (0.0759% mass fraction) at similar conditions. Furthermore, the dissolved PbI2 could be simply recycled by the addition of water as an antisolvent at room temperature. This work provides a green method for the recycling of toxic PbI2 with high performance at mild conditions.